Simulation of gas flow in double-circuit Ranque-Hilsch vortex tube - Noskov, Alexander Semyenovich; Lovtsov, Alexander Viktorovich; Khait, Anatoliy Vilyich (Computational Continuum Mechanics, 2012)
The mathematical model of gas flow in a Ranque-Hilsch vortex tube implemented in the OpenFOAM environment is described. Six types of one- and two-parametric semi-empirical turbulence models are used to simulate the vortex gas flow. It is shown that there is quantitative and qualitative disagreement between the model characteristics of the vortex tube and the experimental data. The obtained results indicate that the applied turbulence model should be modified.
Keywords: Ranque-Hilsch effect; vortex tube; mathematical simulation; turbulence model